ChemInform Abstract: Phospho Sulfonic Acid as an Efficient and Recyclable Solid Acid Catalyst for the Solvent‐Free Preparation of Acylals. Issue 10 (March 2015) - Kalla, Reddi Mohan Naidu; Park, Huiju; Hoang, Trinh Thi Kim; Kim, Il
Abstract The cost effective, mild, and efficient catalyst is recycled and reused in nine additional cycles with only slightly decreasing reaction yields.